2018
DOI: 10.1016/j.yexmp.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of proteins upregulated in hepatocellular carcinoma in patients with alcoholic hepatitis (AH) compared to non-alcoholic steatohepatitis (NASH): An immunohistochemical analysis of candidate proteins

Abstract: Both non-alcoholic steatohepatitis (NASH) and alcoholic hepatitis (AH) can lead to cirrhosis and hepatocellular carcinoma. However, the rate of progression to cirrhosis and tumorigenesis in AH is greater than that in NASH. We asked whether there are differences between the two conditions in the expression levels of proteins involved in the pathogenesis of hepatocellular carcinoma. The proteins tested were presented at the 2017 American Association for the Study of Liver Diseases (AASLD) Liver Meeting as overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…It is well accepted that the rates of those progressing to cirrhosis or HCC annually are lower in the NASH if compared with those in ASH. Our published data support that different molecules or pathways may be involved in ASH compared with NASH during the tumorigenesis [Nguyen et al, 2018][Lu et al, 2018] Our work also showed that the TLR/NFKB/CXCR4/7 [Liu et al, 2014][French et al, 2012] [Nan et al, 2010], PI3K/AKT/mTORC1 signaling pathways [Afifiyan et al, 2017], and Tec kinase signaling pathway connected each other during MDB formation both in ASH and NASH [Afifiyan et al, 2017]. …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It is well accepted that the rates of those progressing to cirrhosis or HCC annually are lower in the NASH if compared with those in ASH. Our published data support that different molecules or pathways may be involved in ASH compared with NASH during the tumorigenesis [Nguyen et al, 2018][Lu et al, 2018] Our work also showed that the TLR/NFKB/CXCR4/7 [Liu et al, 2014][French et al, 2012] [Nan et al, 2010], PI3K/AKT/mTORC1 signaling pathways [Afifiyan et al, 2017], and Tec kinase signaling pathway connected each other during MDB formation both in ASH and NASH [Afifiyan et al, 2017]. …”
Section: Discussionsupporting
confidence: 71%
“…Both ASH and NASH may progress to fibrosis, cirrhosis, and ultimately hepatocellular carcinoma (HCC), about 7–10% of NASH may progress to cirrhosis [Scaglioni et al, 2011] and 0.5% to HCC [Lindenmeyer et al, 2018], while 10–20% of ASH progress to cirrhosis [Schwartz et al, 2012][Dam-Larsen et al, 2004] and 7–10% to HCC [Schwartz et al, 2012], annually. Our previous published work showed that there are different molecules protein changes in ASH compared with NASH [Nguyen et al, 2018][ Lu et al, 2018]…”
Section: Introductionmentioning
confidence: 99%
“…Our published data support that different molecules or pathways may be involved in NASH compared with ASH during the tumorigenesis [12,13]. We showed that the TLR/NFKB/CXCR4/7, PI3K/AKT/mTORC1, and Tec kinase signaling pathways connected with each other during MDB formation both in ASH and NASH [11][12][13][14][15][16][17][18][19][20]24].…”
Section: Discussionsupporting
confidence: 59%
“…The difference in the expression of G9a protein between ASH and NASH groups was statistic significant (Fig. 1) [11,12]. Histidine phosphorylation has broader roles in protein and cellular function including cell cycle regulation, phagocytosis, and tumorigenesis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation